A Development of a Website Application for Train and Bus Ticket Booking in Travel and Tour Services: A Case Study of Safara'al Tour and Travel - Budiman, Tedi; Rosmini (RISTEC : Research in Information Systems and Technology, 2024)
The development of a website application for booking train and bus tickets aims to enhance user experience in travel services, specifically for Safara'al Tour and Travel. This app addresses existing challenges in online ticket booking by offering an intuitive platform for users to select schedules, purchase tickets, and make payments seamlessly. Utilizing the waterfall software development model, the project encompasses user needs analysis, application design, testing, and implementation. Key features include schedule searches, seat selection, online payments, and booking confirmations. The application is expected to improve booking efficiency and user satisfaction while supporting the growth of Safara'al Tour and Travel in the competitive travel industry